Pengaruh Interferensi Bahasa Daerah terhadap Struktur Kalimat Bahasa Indonesia - Juniati Arsiwan (Journal of Language Studies, 2025)
This study examines the influence of regional language interference on the sentence structure of the Indonesian language. Language interference, particularly from regional or local languages, is a common phenomenon in multilingual societies such as Indonesia. The research aims to identify patterns of syntactic interference that emerge when speakers use Indonesian influenced by their native regional languages. Using a qualitative approach, data were collected through interviews, written texts, and recordings of daily conversations among bilingual speakers. The findings reveal that interference occurs in several aspects of sentence structure, including word order, subject-predicate agreement, and the use of conjunctions. Such interference can lead to deviations from standard Indonesian grammar, potentially affecting clarity and mutual understanding. This study highlights the need for increased awareness in both educational and communicative contexts to promote the correct use of standard Indonesian while respecting linguistic diversity.